PTU-130 Endoscopic transluminal vacuum therapy: an alternative method of treating oesophago-gastric defects. (22nd June 2015) - Tan, B; Reddy, S; Rashid, F; Sujendran, V; Safranek, P; Hindmarsh, A; Hardwick, R
Abstract : Introduction: Oesophago-gastric defects which occur as a result of anastomotic leak or spontaneous/iatrogenic perforation often result in severe sepsis. Traditionally, surgery is the mainstay of treatment. However this is associated with high rates of morbidity and mortality and may not always be feasible. We describe our experience of using a minimally invasive method of using an endoscopic transluminal vacuum system to treat these oesophago-gastric defects and deal with the associated mediastinal and abdominal sepsis. Method: An endoscopic vacuum system is created by using an open-pore polyurethane sponge fixed by 0 Silk suture to the distal end of a 12–16 F naso-gastric tube. The sponge tip is trimmed to the desired shape and placed under endoscopic visualisation through the oesophageal defect into the cavity. The vacuum assisted system is kept in position by applying a continuous negative pressure of 125 mmHg allowing the defect cavity to collapse around the sponge. The system is changed every 48–72 h until the cavity shrinks and stable granulation tissue forms a barrier. Results: Between April 2011 and December 2014, 12 patients were treated with an endoscopic transluminal vacuum system for various causes of oesophago-gastric defects after established therapeutic measures had failed or as a primary procedure. Three patients had a spontaneous defect; two patients had an iatrogenic defect; and seven patients had a postoperative oesophageal defect. In 10 of 12 cases, the endoscopic vacuum transluminal system treatment was successful. The therapy was well tolerated with minimal discomfort. Two patients died due to intractable sepsis from the original insult. The rest of the patients are alive and well with a median follow up of nine months. Conclusion: The endoscopic transluminal vacuum system can be used for a wide range of oesophago-gastric defects and, in our experience, successful treatment and healing can be achieved. It provides a new and useful treatment option in the management of these challenging patients. Disclosure of interest: None Declared.